Understanding the role of coaches in supporting the mental health of elite athletes - Sankey, C.; Wallace, Lee.; Caperchione, C. M. (Journal of Science and Medicine in Sport, 2023)
Objectives Elite sport coaches often rely on their discretion when assisting athletes struggling with mental health, with clear guidelines yet to be broadly adopted. This study aimed to explore how coaches perceive their role in athlete mental health and their role clarity.